Microenvironmental changes in the progression from adenocarcinoma in situ to minimally invasive adenocarcinoma and invasive lepidic predominant adenocarcinoma of the lung. (October 2016) - Naito, Masahito; Aokage, Keiju; Saruwatari, Kouichi; Hisakane, Kakeru; Miyoshi, Tomohiro; Hishida, Tomoyuki; Yoshida, Junji; Masato, Sugano; Kojima, Motohiro; Kuwata, Takeshi; Fujii, Satoshi; Ochiai, Atsushi; et al.
Highlights: The cancer cells and stromal cells are immunostained in LPA. Invasive potential of cancer cells is increased in noninvasive component of MIA. At the progression from MIA to LPA-S, microenvironmental molecular changes occur. Abstract: Objectives: Invasive lepidic predominant adenocarcinoma (LPA) of the lung is thought to progress in a stepwise fashion from adenocarcinoma in situ (AIS) and minimally invasive adenocarcinoma (MIA). The aim of this study was to investigate the microenvironmental changes during the development from AIS to LPA. Materials and methods: Clinicopathological characteristics of AIS (n = 51), MIA (n = 59), LPA smaller than 3 cm (LPA-S, n = 113), and LPA larger than 3 cm (LPA-L, n = 47) were analyzed. We then evaluated the expression levels of epithelial-mesenchymal transition (EMT)-related molecules (E-cadherin, S100A4), invasion-related molecules (laminin-5, ezrin), stem-cell-related molecules (ALDH-1), and growth factor receptors (c-Met, EGFR) in cancer cells of each group (n = 20). The number of tumor-promoting stromal cells, including podoplanin-positive cancer-associated fibroblasts (PDPN+ CAFs), CD204-positive tumor-associated macrophages (CD204+ TAMs), and CD34+ microvessel cells, were also analyzed. Results: No significant difference in these characteristics was found between LPA-S and LPA-L. Laminin-5 expression in the non-invasive carcinoma component of MIA was significantly higher than that of AIS (p < 0.001). During the progression from MIA to LPA-S, the expression level of laminin-5 in the invasive carcinoma component was significantly elevated (p < 0.01). Moreover, tumor-promoting stromal cells were more frequently recruited in the invasive area of LPA-S (PDPN+ CAFs; p < 0.05, CD204+ TAMs; p < 0.001, CD34+ microvessel; p < 0.05). Ezrin expression in the invasive carcinoma component of LPA-L was significantly increased (p < 0.05) compared to LPA-S; however, the number of tumor-promoting stromal cells were not different between these two groups. Conclusion: Our current results indicated that microenvironmental molecular changes occur during the progression from MIA to LPA-S and suggested that this process may play an important role in disease progression from AIS to LPA.